The narrative imaginative between the opinions of the ancients and moderns: A study in the historical frameworks of the concept - Khalif, Ghanim AbdulSada; Hassan, Essam Asal (Al-Adab Journal, 2021)
The narrative visualizer is a mental conception that can be compatible with reality or contradict with it, and writers and critics have realized from ancient times the importance of imagination and imagination in the process of literary creative creation, and when we put our hands on different meanings and definitions of idiomatic significance for some thinkers, rhetoric and critics, we found that they differed in each other in determining What it is and the difference between one’s perception of the other from the truth of this concept, each gives his opinion according to his doctrine, his knowledge and his personal ideology, starting from the old philosophical thought and ending with modern philosophical and critical thought, and from here we will try to shed light on the historical frameworks of the narrative concept, following the chronology of the most important critical opinions And the philosophical that dealt with this concept.